Pengembangan Media pembelajaran berbasis Website untuk siswa kelas XI pada mata pelajaran Informatika - Tegela, Nelly; Mulyanto, Arip; Polin, Muchlis (Jurnal Vokasi Sains dan Teknologi, 2024)
This research is motivated by the main problem in SMA Negeri 1 Tilamuta Class XI, which is the lack of learning media that can be accessed and operated directly without having to download the application first. This research has three main objectives, namely to identify the need for web-based learning media, to design such media for the computer science curriculum, and to evaluate its feasibility. This research uses the ADDIE model with five stages, namely analysis, design, development, implementation and evaluation. The results show that the web-based learning media developed for computer science subjects, especially computer network and internet materials, can effectively enhance the learning process. These media can be a valuable tool for students and teachers. Feasibility testing by materials experts shows a high level of validity, namely 100%, which means that it is very feasible. Media experts gave a score of 96.6%, which means it is very feasible. In addition, user evaluation using the System Usability Scale (SUS) resulted in an impressive score of 88.3%, which means very good. In conclusion, the website based learning media for computer network and internet material has been confirmed as a practical and effective learning resource for teaching and learning activities in Class XI SMA Negeri 1 Tilamuta